Engineering properties of natural fibre-reinforced one-part geopolymer concrete - Ayeni I.S.; Lim N.H.A.S.; Samad M. (Elsevier Ltd, 2025)
Environmental concerns and the desire for improved performance in building construction have led to a great deal of attention being paid to developing sustainable construction materials. The engineering characteristics of natural fibre-reinforced one-part geopolymer concrete (NFROPGC), a novel material that combines strong mechanical qualities and offers significant environmental advantages, are examined in this work. Activated by a dry alkali source (Sodium meta?Silicate Anhydrous), one-part geopolymer concrete is more sustainable and easier to use than two-part geopolymer concrete. Fibres from kenaf, coconut, and oil palm measuring 25 mm and containing 0 %, 0.75 %, and 1 % were utilised. The chosen fibres were treated with an alkaline solution of 5 % concentration to enhance their performance. The engineering properties of natural fibre-reinforced one-part geopolymer concrete were measured by determining its workability, compressive, flexural, split tensile, impact resistance strengths, MOE, Poisson's ratio, and water absorption. Also, its morphology was studied under the scanning electron microscope. The flexural, splitting tensile strengths and MOE were improved by including 0.75 % natural fibre in one-part geopolymer concrete. Kenaf, coconut, and oil palm fibre-reinforced one-part geopolymer concrete showed increased flexural strengths from 4.93 MPa to 7.87 MPa, 4.11 MPa to 6.04 MPa, and 4.02 MPa to 5.85 MPa, respectively, while splitting tensile strengths of kenaf, coconut, and oil palm fibre-reinforced one-part geopolymer concrete increased from 3.3 MPa to 4.95 MPa, 3.25 MPa to 4.37 MPa, 2.95 MPa to 3.79 MPa, respectively and the MOE of kenaf, coconut, and oil palm fibre-reinforced one-part geopolymer concrete increased from 37.77 GPa to 44.04 GPa, 37.77 GPa to 42.79 GPa, and 37.77 GPa to 39.61 GPa, respectively. The optimum impact resistance strengths of the reinforced geopolymer concrete for kenaf fibre, coconut fibre, and oil palm fibre were obtained at 1 % fibre content with increments of 122.11 %, 98.33 %, and 88.33 %, respectively. However, fibre-reinforced one-part geopolymer concrete's compressive strength and workability reduced slightly as fibre content rose. The SEM results demonstrate how well fibres fill voids and bridge cracks in one-part geopolymer concrete. Future studies will focus on long-term performance evaluations and scaling up for industrial buildings. ? 2024 Elsevier Ltd